Detection and Classification of MRI Brain Images For Head/Brain Injury Using Soft Computing Techniques - Burje, Shrikant; Rungta, Sourabh; Shukla, Anupam (Research journal of pharmacy and technology, 2017)
N. Hema Rajini , R. Bhavani Classification of MRI brain images using k-nearest neighbor and artificial neural network, International Conference on Recent Trends in Information Technology (ICRTIT)2011, IEEE DOI: 10.1109/ICRTIT.2011.5972341 11. Emin Tagluk, M., M. Akin, and N. Sezgin, "Classification of sleep apnea by using wavelet transform and artificial neural networks", Expert Systems with Applications, Vol. 37, No. 2, 1600-1607, 2010. Chaplot, S., L. M. Patnaik, and N. R. Jagannathan, "Classification of magnetic resonance brain images using wavelets as input tosupport vector machine and neural network," Biomedical Signal Processing and Control, Vol. 1, No. 1, 86-92, 2006. N. V. S. Natteshan, J. Angel Arul Jothi, " Automatic Classification of Brain MRI Images Using SVM and Neural Network Classifiers" , Advances in Intelligent Informatics, Volume 320 of the series Advances in Intelligent Systems and Computing pp 1930 15.